THE ROLE OF RECRUITMENT AND SELECTION WITH REFERENCE TO HYUNDAI PVT LTD, HYDERABAD - SK.GALEEB, P.Girija sree (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Human resources planning means deciding the number and type of the human resources required for each job, unit and the total capacity for a particular future date in order to carry out organizational activities. Human resources planning as "a process by which an organization should move from its current man power position to its desired manpower position. Though planning management strives to have the right number and right kind of people at the right place at the right time, doing things, which result in both the organization and the individual receiving maximum long run benefit. Once the required number and the kind of human resources are determined, the management has to find places where required human resources are available and also work out strategies for attracting them towards the organization before selecting suitable candidates for jobs. This process is generally known as recruitment. Technically speaking the function recruitment precedes the selection function and it includes only finding, developing the sources of prospective employees and attracting them to apply for jobs in an organization